Culture wars irregular warfare, culture policy, and adaptation in the marine corps - Holmes-Eber, Paula (Stanford University Press, 2014)
Culture in Conflict: Irregular Warfare, Culture Policy, and the Marine Corps examines the conflicted trajectory of the Marine Corps' efforts to institute a radical culture policy into a military organization that is structured and trained to fight conventional wars. More importantly, however, it is a compelling book about America's shifting military identity in a new world of unconventional warfare.